Community Development Agreements - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
This note provides guidance on negotiating, designing, and implementing community development agreements between investors and local communities. Some investors, in particular those thatoperate in remote rural areas, have made significant contributions to local development through social development programs. Their effectiveness and the manner in which they are implemented depend on the context and the capacity of the investor. The most successful programs include localcommunities in making decisions about scope, require investors to make binding commitments, and support rather than supplant governmental responsibilities.